Termorregulação da bolsa escrotal associada à qualidade do sêmen de caprinos na região Semi-árida - Costa, Leonardo Lelis de Macedo (Universidade Federal Rural do Semi-Árido, 2010)
We evaluated the Thermoregulation of the scrotum associated with quality semen of goats grazed in the meteorological conditions of the semi-arid. 10 goats were used. There were 5 observations, with four days of interval. Five groups were formed, each group was collected in different hours (8am, 10am, 12pm, 2pm and 4pm). The skin surface body temperatures (SSBT) and the scrotum (ST), respiratory rate and rectal temperature were recorded. Heat loss by cutaneous evaporation was measured from the H2O/CO2 analyzer, in the body was used a vented cap and in the scrotum was developed a ventilated capsule adapted for that region. The area of scrotum was determined through analysis of regression. Semen was collected via an artificial vagina and evaluated macro-and microscopically. Irradiance, wind speed, air, wet bulb and black globe temperatures were recorded. The Statistical analysis was based on the method of least squares. For analysis of quality of the semen it was used a 5x5 Latin square design. The SSBT 34.5 ±0.92ºC and ST was 33.5 ±0.36ºC, showing a difference of 1ºC between those regions. The latent heat loss was 57.3 ±18.0 W.m-2 for body surface and 49.4 ±15.0 Wm-2 to the scrotum. Semen samples were considered of good quality at all times and days of collection. The conclusion was that the difference between the surface temperatures derive from a combination of mechanisms which involve thermoregulation of the scrotum, and the animals can be utilized for breeding at any time of the day.
Thermoregulation of the scrotum associated with quality semen of goats in semi-arid region
Keywords: goat semen; thermoregulation; scrotum; cutaneous evaporation; sêmen caprino; termorregulação; bolsa escrotal; evaporação cutânea; CIENCIAS AGRARIAS::MEDICINA VETERINARIA